(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Тhe article conducts a theoretical study of the effect of the length of the pegs on the cleaning effect of the raw cotton cleaner. The conducted theoretical research shows that for more loosened raw cotton, a length of 25mm and a diameter of 8mm are sufficient for splitting.